Aluminum-silicon coatings on austenitic stainless steel (AISI 304 and 317) deposited by chemical vapor deposition in a fluidized bed - José Luddey Marulanda Arevalo; Francisco Javier Pérez Trujillo; Saúl Isaac Castañeda (Ingeniería e Investigación, 2014)
Aluminum-silicon coatings were deposited onto stainless steels AISI 304 and AISI 317. The deposition was performed at 540°C with a ratio of active gases HCl/H2 of 1/15.3; argon was used as a carrier gas. The bed of the FBR-CVD process consisted of 2.5 g aluminum powder, 7.5 g silicon powder and 90 g alumina. After the coatings were deposited, each sample was given a heat treatment to improve its mechanical properties and oxidation behavior by diffusing the alloying elements. Thermodynamic simulation was performed with Thermo-Calc software to investigate the composition of the deposited material. The coated and uncoated specimens were exposed to temperatures of 750ºC in an atmosphere where the vapor was transported to the samples using a flow of N2 of 40 ml/min and 100% water vapor (H2O). The coated specimens gained little weight during the thousand hours of exposure and will thus guard against a corrosive attack compared to the uncoated substrates. In addition, the coated stainless steels show an oxidation rate with a logarithmic trend while the uncoated steel oxidation rate showed a linear trend.